Linking positive emotions and academic performance: The mediated role of academic psychological capital and academic engagement - Carmona-Halty, Marcos; Salanova, Marisa; Llorens, Susana; Schaufeli, Wilmar B. (Current psychology (New Brunswick, N.J.), 2021)
The present study examined the relationship between positive emotions and academic performance, and the mediated role played by academic psychological capital and academic engagement, in a sample of 497 Chilean high school students. Participants´ ages ranged from 14 to 17 years old, with a mean of 15.71 (SD = 1.15). Findings supported our hypothesized model that academic psychological capital and academic engagement mediate the relationship between positive emotions and academic performance (GPA). The proposed model has theoretical implications for future research and practical implications for school settings. The promotion of positive emotions in students is a relevant challenge for principals, teachers, and parents in attempting to build academic psychological capital and academic engagement, which in turn may lead to higher academic performance.